Analisis Website PT. Kereta Api Indonesia Menggunakan Web Quality Evaluation Method (WEBQEM) untuk Kualitas dan Layanan dari Sisi Pengguna - Merlin Diana; Novian Ikhsan (Lembaga Pengembangan Kinerja Dosen, 2025)
Train transportation is one of the most popular forms of transportation among Indonesians. One of the advantages of train transportation is that affordable prices and relatively faster travel times are one of the factors that make this transportation so popular with the public. As one of the public transportation companies that is quite popular with the public, PT Kereta Api Indonesia always strives to provide the best service to meet the needs of its users. Therefore, PT Kereta Api Indonesia provides website services that can be accessed by users. The WEBQEM method is one method to determine the quality of a website from the assessment of its users. The WEBQEM method includes an assessment of the characteristics of Usability, Functionality, Reliability, and Efficiency. The results of the study obtained the results of several factors that according to website users need to be improved such as users disagree if users who only occasionally use the PT K.A.I website will like to use the PT K.A.I website.